Swart protes versus wit teenstand: die politiek van regse blanke vrese, 1982-1987 - Du Bruyn, Derek; Wessels, André (Faculty of Humanities, University of the Free State, 2010)
In this article the interaction between black protest politics and white resistance is discussed by tracing the history of the politics of fear in right-wing quarters in South Africa in the years 1982 to 1987. In 1982 the founding of the Conservative Party (CP) under Dr Andries Treurnicht heralded a new era in white politics in South Africa, and five years later the CP became the official opposition in the white Parliament. In-between there was a referendum in 1983 on the Tricameral Parliament; a new constitution was adopted; there was an increase in the number of acts of terror committed by Umkhonto weSizwe (the armed wing of the African National Congress), and mass action by the United Democratic Front. More and more whites withdrew to the “laager”; their politics became even more reactionary, and their society more militarised. The National Party, the CP and the Herstigte Nasionale Party propaganda exploited white fears, but for different reasons. The politics of fear indeed reigned supreme in these years.
Keywords: Black protest politics; White resistance; Political parties; Right-wing politics